A survey paper on privacy issue in cloud computing - Aldeen, Yousra Abdul Alsahib S (Maxwell Science Publications, 2015)
In past few years, cloud computing is one of the popular paradigm to host and deliver services over Internet. It is having popularity by offering multiple computing services as cloud storage, cloud hosting and cloud servers etc., for various types of businesses as well as in academics. Though there are several benefits of cloud computing, it suffers from security and privacy challenges. Privacy of cloud system is a serious concern for the customers. Considering the privacy within the cloud there are numerous threats to the user's sensitive data on cloud storage. In this study, we give a survey on numerous works on cloud computing, provide a survey on several research on cloud privacy issues, classify current solutions for privacy issues in cloud environments as architectures, approaches and methods and the advantages and disadvantages of current studies are tabulated. Moreover, it also discusses open research challenges and recommends future research directions. The main goal of this study is to offer a better understanding of the privacy challenges of cloud computing and to focus on current gaps to fulfil the privacy issue.